If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4x+45=5(3x-2)
We move all terms to the left:
4x+45-(5(3x-2))=0
We calculate terms in parentheses: -(5(3x-2)), so:We get rid of parentheses
5(3x-2)
We multiply parentheses
15x-10
Back to the equation:
-(15x-10)
4x-15x+10+45=0
We add all the numbers together, and all the variables
-11x+55=0
We move all terms containing x to the left, all other terms to the right
-11x=-55
x=-55/-11
x=+5
| ?x5=45 | | x2+8=129 | | (9x+16)+(9x+16)=(19x+3) | | -7=3(v-1)+2(-3v-2) | | 9(s-1)=45 | | 4x+2+5x-12=90 | | 4x–3+8–2x=33 | | 2(5x+-3)=24 | | .25(n-12)=-2(n-3) | | -2(3r-10)+8r=7r+20+7r | | x3-5=3 | | -5x+7=-5+3 | | 13-x-x=-1 | | 16x-4x-33=15 | | 5v+1-3(-2v-1)=2(v-4) | | 6-1x=8.25-1x | | -7=1.97+h | | 14x-6=4x+34 | | 9(n-4)=56 | | 1.7(f+1.4)=9.35 | | 1x/7-4/3=-1/2 | | -1/3(9z+42)-5z=-70 | | 3y–15=(–21) | | .18=5a-2a+3 | | t-7=83 | | 10x-12=6x-610x−12=6x−6 | | 6x-50=1x+70 | | 274=63-y | | -8r-3=-1r | | 17x-19=60 | | 11+150=-8(-3w-3)-7 | | 3p+6=-(1+4p) |